Peran Media Sosial Dengan Platform Tiktok Dalam Mempengaruhi Etika Bangsa Indonesia - Mulawarman, Mulawarman (Jurnal Ilmu Pemerintahan, 2025)
The rapid development of social media, particularly TikTok, has had a significant impact on the ethics of Indonesia’s young generation. TikTok, as a short-video sharing platform, functions not only as a medium of entertainment but also as a forum for self-expression and identity formation. However, uncontrolled use can generate negative effects such as addiction, reduced productivity, psychological health issues, and the deterioration of ethical values and social norms. The purpose of this article is to examine the role of TikTok in shaping the mindset and behavior of Indonesian youth through a qualitative literature research approach with explanatory analysis. The findings indicate that TikTok provides opportunities for digital creativity and literacy development, but its use must be accompanied by ethical awareness to avoid undermining cultural identity and national morality. Therefore, strong digital literacy and monitoring from multiple stakeholders are required to create a healthy and responsible digital environment.